2019
DOI: 10.1038/s41598-019-39820-z
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic model systems used to emulate processes occurring during soft particle filtration

Abstract: Cake layer formation in membrane processes is an inevitable phenomenon. For hard particles, especially cake porosity and thickness determine the membrane flux, but when the particles forming the cake are soft, the variables one has to take into account in the prediction of cake behavior increase considerably. In this work we investigate the behavior of soft polyacrylamide microgels in microfluidic model membranes through optical microscopy for in situ observation both under regular flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 31 publications
(30 reference statements)
0
19
0
Order By: Relevance
“…The channels of the microfluidic devices used in this work have a variety of entrance angles. In previous work 23 , we found that the entrance angles do not have an influence on overall clogging behavior of micrometer-sized particles that are smaller than the pore. Here we investigate larger particles in detail.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…The channels of the microfluidic devices used in this work have a variety of entrance angles. In previous work 23 , we found that the entrance angles do not have an influence on overall clogging behavior of micrometer-sized particles that are smaller than the pore. Here we investigate larger particles in detail.…”
Section: Resultsmentioning
confidence: 66%
“…Microgels were synthesized and characterized as described in previous work 23 . Polyacrylamide (pAAm) microgels are used as model particles for the channel clogging experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the filtration of soft particles is more complex. Soft particles can undergo deformation, interpenetration, and compression 5 , such that the resulting filter cakes deform partly reversibly and irreversibly during filtration 6 . Additionally, the particles in a soft cake can rearrange their position due to deformation and often create crystalline cake regions, such that the cake becomes strongly non-isotropic 7 9 .…”
Section: Introductionmentioning
confidence: 99%